Innovations in Teaching History (University of London Press, 2024)
An essential teaching companion offering practical strategies for enhancing learning for all teachers of history in higher education. The study of the eighteenth century has been a growth area in university research and teaching in recent decades. Although widely taught in history departments, the eighteenth century also presents challenges, including new students’ unfamiliarity with the period, the theoretical and interdisciplinary nature of the critical writings, and extensive online source material requiring digital skills for its evaluation. Focusing on pedagogical innovation and current developments in the discipline, this collection of essays reflects on how we teach the history of the long eighteenth century, exploring current subfields such as histories of material culture, the senses, gender, crime and empire. It presents practical case studies showcasing how novel teaching methods can be employed in the classroom that promote active learning and invite students to think critically about the nature of their discipline. Methods covered include decolonising the curriculum, digital history, transferable skills, engaging with objects, working in non-classroom settings and multisensory approaches. Grounded in real academic practice, this is a valuable guide for all history educators, whether specialising in the eighteenth century or beyond.